Family Spaces of Socialisation Dialogue in the Times of Digital Revolution - Witold Wrzesień (Jesuit University Ignatianum in Krakow, 2022)
RESEARCH OBJECTIVE: The aim of the article is a theoretical diagnosis of the influence of the pace of recent civilisation changes on a selected fragment of the socialisation process in the family. The course of analysis is the specificity of the relationship between parents and adolescent children (aged 15-18), including an attempt to explore the modifications occurring in these areas resulting from the development of information technology. THE RESEARCH PROBLEM AND METHODS: The research problem of this paper is an attempt to answer the question: To what extent do new inter- and intra-generational divisions - appearing as a result of rapid civilisation changes generated by the development of information technologies - modify the socialising dialogue in relations between parents and adolescent children? The research method used was a selective analysis of theoretical works and research reports from sociology, psychology, psychiatry, neurobiology and information technology. THE PROCESS OF ARGUMENTATION: The article presents selected elements of the conceptual model used to analyse the world of contemporary generations. It includes the new division into the world of the present past and the world of the present future, together with their new inhabitants - people of the past and people of the future.  RESEARCH RESULTS: As a consequence of the increasingly deepening division of the world of generations, constructing a socialisation dialogue in the relationship between parents and adolescent children has become more complicated. The confrontational-verifying influence of intra-familial socialisation concerning the areas of secondary socialisation  is noticeably losing its significance. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The modifications of intergenerational relations within the family, occurring as a result of rapid civilisation changes, result in an "unfinished", incomplete socialisation process of adolescent children, heading towards an unknown form of adulthood with this new cultural capital.